Comparison of upper and lower lip position, length and thickness in sagittal and vertical malocclusion - Hafiza Maryam Khurshid; Rizwan, Sadia; Ahmed, Imtiaz; Hafiz Taha Mehmood; Nagani, Nasreen Iqbal; Tanvir, Faiqa (Journal of the Pakistan Medical Association, 2023)
This study aimed to compare the upper and lower lips position, length, and thickness in different malocclusions, in randomly selected 180 patients’ pre-treatment lateral cephalograms. The subjects were grouped sagittally by using Steiner’s analysis and Wits appraisal and vertically based on Frankfort horizontal and mandibular plane (FHMP) angle and lower facial height. One-way ANOVA was applied to compare the upper and lower lip positions, thickness, and length in sagittal and vertical malocclusion and independent sample T test was applied for comparison between genders among soft tissue variables. Post-hoc Dunnett T3 was performed for comparison of lip variables in adjacent malocclusion groups. The level of significance was not less than or equal to 0.05 The anteroposterior position of the upper and lower lips with respect to E and S planes and upper and lower lip thicknessaried significantly (p < 0.05) in all classes of sagittal malocclusion, —Continue